Conservation Geomatics - Edoardo Mollica; Domenico Enrico Massimo; Michelangela Vescio; Antonino Barbalace; Antonino Barbalace; Antonia Rita Castagnella; Antonio Pietro Paolo Massimo; Aurelio Mercurio (GEOmedia, 2004)
Conservation Geomatics